Peranan Komisi Pemilihan Umum Kabupaten Lombok Timur dalam Rangka Meningkatkan Angka Partisipasi Pemilih Penyandang Disabilitas di Wilayah Kabupaten Lombok Timur: Menyambut Pemilu Serentak Tahun 2024 - SH., MH, Taharudin (Jurnal Bawaslu Provinsi Kepulauan Riau, 2023)
This study aims to find out the extent to which the General Election Commission (KPU) of East Lombok Regency plays a role in increasing the participation rate of voters with disabilities. The research method used is a descriptive method with a qualitative approach, One of the most important stages in elections whose purpose is to accommodate the political rights of persons with disabilities is the stage of socialization of political education for people with disabilities. If you look at the 2019 elections where the participation rate of persons with disabilities who exercised their voting rights in the East Lombok Regency area reached 67.11%. The East Lombok Regency KPU plays a role in providing political education for persons with disabilities by holding socialization and discussion forums with persons with disabilities, creating the Segare Anaq Election Smart Home, and also increasing cooperation with organizations and foundations for persons with disabilities in East Lombok. There are several obstacles faced by the East Lombok KPU, namely combining material with methods in providing political education and obstacles in the process of collecting data on the number of persons with disabilities.